ChemInform Abstract: Au10Mo4Zn89: A Fully Ordered Complex Intermetallic Compound Analyzed by TOPOS. Issue 50 (10th December 2013) - Jana, Partha P.; Pankova, Arina A.; Lidin, Sven
Abstract The title compound is synthesized from the elements (silica ampule, 1273 K for 2 h followed by annealing at 703 K for 5 d) and characterized by single crystal XRD, EDX, and TB‐LMTO‐ASA calculations.